2016
DOI: 10.1080/10669817.2016.1260674
|View full text |Cite
|
Sign up to set email alerts
|

The effect of direction specific thoracic spine manipulation on the cervical spine: a randomized controlled trial

Abstract: 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…1 , we screened 3,288 articles, from which nine were included for analysis 23 31 . One additional article was found using backward citation tracking 32 , which resulted in ten included studies. All articles were in English and published between 2003 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 , we screened 3,288 articles, from which nine were included for analysis 23 31 . One additional article was found using backward citation tracking 32 , which resulted in ten included studies. All articles were in English and published between 2003 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…All articles were in English and published between 2003 and 2020. All but three authors 25 27 reported if there were any conflicts of interest, and four reported that they received funding 23 , 24 , 31 , 32 . We contacted the authors of three articles 30 , 33 , 34 with insufficient data to estimate effect sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations